MODELS AND METHODS FOR IMPROVING THE CONSTRUCTION OF MEDICAL INFORMATION SYSTEMS - LEVKIVSKYI, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The digitalization of society requires new solutions in all areas of human activity. The development of information technologies has created the preconditions for digitization and digital transformation of business and society as a whole. The Covid-19 coronavirus pandemic and subsequent full-scale Russian invasion have created challenges for society and medicine in particular and led to rapid digitalization. The use of remote diagnostic technologies has gained unprecedented momentum. Telemedicine, cloud technologies, modern digital monitoring and diagnostic devices, mobile applications, and medical information systems have become an integral part of providing qualified medical care. The creation of an electronic healthcare system and its improvement is a strategic task for the leadership of modern developed countries, including Ukraine. This article presents ways to improve medical information systems used in the healthcare sector of Ukraine by improving the module for remote diagnosis of patients' condition and implementing a module for intellectual analysis and prediction of comorbidities. The remote diagnosis module is proposed to be supplemented with "questionnaires" adapted to the doctor's specialization. The module of intellectual analysis and prediction of comorbidities is proposed to be built using data mining. The models of these modules are presented. The set of proposed models and methods for improving the construction of medical information systems increases the level of awareness of doctors to establish a diagnosis and make decisions on patient prescriptions, remote monitoring of the patient's condition and prediction of the development of concomitant diseases. The proposed models and methods are ready for practical implementation by software.
Keywords: diagnostics; digitalization; information technology; medical information system; models; methods; healthcare; telemedicine